Principal Leadership and Work Discipline as Predictors of Teacher Performance: A Quantitative Study in Indonesian Public Junior High Schools - Meditran Meditran; Nur Ahyani; Mahasir Mahasir (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examines the influence of principal leadership and teacher work discipline on teacher performance in public junior high schools in Banyuasin III District, Indonesia. Teacher performance is a critical determinant of educational quality, yet empirical evidence regarding its predictors in Indonesian junior high school contexts remains limited. Using a quantitative approach with a survey design, data were collected from 106 teachers selected through Slovin formula sampling from a population of 145 teachers. Multiple linear regression analysis was employed to test the hypotheses. The findings reveal that: (1) principal leadership has a positive and significant effect on teacher performance (β = 0.487, p < 0.05); (2) teacher work discipline has a positive and significant effect on teacher performance (β = 0.646, p < 0.05); and (3) both variables simultaneously explain 44.6% of the variance in teacher performance (F = 41.78, p < 0.05). These results underscore the importance of effective school leadership and consistent work discipline in enhancing teacher professionalism. The study contributes empirical evidence to educational management literature and offers practical recommendations for school principals and education policymakers in developing strategies for sustainable teacher performance improvement. Future research should explore mediating variables and conduct qualitative investigations to deepen understanding of these relationships.